Structural insights into SOD1: from in silico and molecular dynamics to experimental analyses of ALS-associated E49K and R115G mutants - Hosseini Faradonbeh, Seyed Mahdi; Seyedalipour, Bagher; Keivan Behjou, Nasrin; Rezaei, Kimiya; Baziyar, Payam; Hosseinkhani, Saman (Frontiers in Molecular Biosciences, 2025)
Protein stability is a crucial characteristic that influences both protein activity and structure and plays a significant role in several diseases. Cu/Zn superoxide dismutase 1 (SOD1) mutations serve as a model for elucidating the destabilizing effects on protein folding and misfolding linked to the lethal neurological disease, amyotrophic lateral sclerosis (ALS). In the present study, we have examined the structure and dynamics of the SOD1 protein upon two ALS-associated point mutations at the surface (namely, E49K and R115G), which are located in metal-binding loop IV and Greek key loop VI, respectively. Our analysis was performed through multiple algorithms on the structural characterization of the hSOD1 protein using computational predictions, molecular dynamics (MD) simulations, and experimental studies to understand the effects of amino acid substitutions. Predictive results of computational analysis predicted the deleterious and destabilizing effect of mutants on hSOD1 function and stability. MD outcomes also indicate that the mutations result in structural destabilization by affecting the increased content of β-sheet structures and loss of hydrogen bonds. Moreover, comparative intrinsic and extrinsic fluorescence results of WT-hSOD1 and mutants indicated structural alterations and increased hydrophobic surface pockets, respectively. As well, the existence of β-sheet-dominated structures was observed under amyloidogenic conditions using FTIR spectroscopy. Overall, our findings suggest that mutations in the metal-binding loop IV and Greek key loop VI lead to significant structural and conformational changes that could affect the structure and stability of the hSOD1 molecule, resulting in the formation of toxic intermediate species that cause ALS.